Diseño e implementación de un sistema fuzzy-pid pera el control del ángulo de inclinación del panel solar monocristalino de 30 watt - Recalde Regalado, Néstor Xavier (2014)
In the project the difference by putting a solar panel on static mode compared with a solar panel in dynamic mode, the dynamic mode solar panel system works with a Fuzzy-PID controller is implemented in a microcontroller is shown, this control system is to position the solar panel in a good position to take advantage of solar radiation and thus, it is possible to store the energy collected by the solar panel in a battery.